Predictors of overall and disease-free survival in metastatic castration-resistant prostate cancer patients receiving 225Ac-PSMA-617 radioligand therapy - Sathekge, Mike; Kratochwil, Clemens; Giesel, Frederik L. (Journal of nuclear medicine, 2020)
Metastatic prostate carcinoma overexpresses prostate-specific membrane antigen (PSMA), making this antigen a suitable target for radioligand therapy of the disease. Here we report on our experience with a series of 73 castration-resistant prostate carcinoma patients treated with 225Ac-PSMA-617, identifying variables predictive for overall survival (OS) and progression-free survival (PFS) after 225Ac-PSMA-617 treatment. Methods: 225Ac-PSMA-617 was administered to patients who had metastatic castration-resistant prostate carcinoma and who had exhausted available therapy options for their disease. Full blood count, glomerular filtration rate, and liver function test were obtained at baseline and on follow-up for evaluation of toxicity. 68Ga-PSMA PET/CT was obtained at baseline, before every treatment cycle, and on follow-up for selection of patients for treatment, to determine the activity of the treatment agent to be administered, and for response assessment. Serial prostate-specific antigen (PSA) was obtained for PSA response assessment. Results: Seventy-three men (mean age, 69 y; range, 45-85 y) with metastatic castration-resistant prostate carcinoma were treated with 210 cycles of 225Ac-PSMA-617. In 70% of patients, a PSA decline of greater than or equal to 50% was obtained; 82% of patients had any PSA decline. In 29% of patients, all lesions on 68Ga-PSMA PET resolved in response to treatment. During follow-up, 23 patients experienced disease progression, whereas 13 patients died from their disease. The estimated median PFS and OS were 15.2 mo (95% CI, 13.1-17.4) and 18 mo (95% CI, 16.2-19.9), respectively. In univariate analyses, factors such as baseline PSA, any PSA decline, PSA decline of greater than or equal to 50%, prior chemotherapy, prior radiation therapy, and baseline hemoglobin level were associated with longer PFS and OS (all Ps < 0.05). In multivariate analyses, there was a negative association between prior 177Lu-PSMA therapy and PFS, and a positive association between PSA decline of greater or equal to 50% and PFS. Only a PSA decline of greater than or equal to 50% remained significantly associated with OS on multivariate analyses. Xerostomia was seen in 85% of patients but was not severe enough to warrant discontinuing treatment. Anemia was seen in 27 patients; no patients had grade IV bone marrow toxicity. Renal failure of grade III or IV was seen in 5 patients with baseline renal impairment. Conclusion: In this study, a PSA decline of greater than or equal to 50% after treatment with 225Ac-PSMA-617 was proven by multivariate analyses to be significantly associated with OS and PFS. Furthermore, previous 177Lu-PSMA treatment was negatively associated with PFS in both univariate and multivariate analyses.